Extension of legitimacy and its legal problems - Ismail Namiq Hussein (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Commitment to the prescribed period of legitimacy is the basis for the existence of legitimacy, and to add value to it, and contribute to the stabilization of stability and governance. But sometimes, under undemocratic regimes, the extension of legitimacy is resorted to on the pretext of weak and deceptive pretexts and false legal grounds, leading to the weakening of legitimacy itself, and may result in grave legal and political implications for stability and collective security.